Nasal Allergy Clinic in Chiba National Hospital - TAKEMIYA, Sanzo; YAMAGUCHI, Munehiko; YAJIMA, Hisao (Japanese Journal of National Medical Services, 1974)
We introduce our nasal allergy clinic through 67 cases we could ovserve from Jan, to June'67. When allergen was discovered we chose hyposensitization (most of them were house dust) with rather good effeci. When allergen could not be found, we tried to use Histaglobin about 10 cases. But the drug seemed to be not of f ectiv. When the attack is severe, in many hospitals Vidian Neurectomy is tried but this operation is rather difficult and so we tried ganglion block using fenol or alcohol. We injected the drug from foundation of middle turbinate in Fossa pterygoparatine and it inhibited nasal allergy attacks more than 6 months and side effect was negligeable. For children or seasonable nasal allergy patients, we tried to use Disodium Cromogricate (Intal) spraying in nasal cavity, and recognized some results.